Genetic polymorphism of high-molecular-weight glutenin subunit loci in bread wheat varieties in the Pre-Ural steppe zone - A. A. Galimova; A. R. Kuluev; K. R. Ismagilov; B. R. Kuluev (Вавиловский журнал генетики и селекции)
High-molecular-weight glutenins play an important role in providing high baking qualities of bread wheat grain. However, breeding bread wheat for this trait is very laborious and, therefore, the genotyping of variety samples according to the allelic composition of high-molecular-weight glutenin genes is of great interest. The aim of the study was to determine the composition of high-molecular-weight glutenin subunits based on the identification of the allelic composition of the Glu-1 genes, as well as to identify the frequency of the Glu-1 alleles in bread wheat cultivars that are in breeding work under the conditions of the Pre-Ural steppe zone (PSZ). We analyzed 26 winter and 22 spring bread wheat varieties from the PSZ and 27 winter and 20 spring varieties from the VIR collection. Genotyping at the Glu-A1 locus showed that the Ax1 subunits are most common in winter varieties, while the predominance of the Ax2* subunits was typical of spring varieties and lines. In the Glu-B1 locus, the predominance of alleles associated with the production of the Bx7 and By9 subunits was revealed for both winter and spring varieties. In the case of the Glu-D1 gene, for all the wheat groups studied, the composition of the Dx5+Dy10 subunits was the most common: in 92.3 % of winter and 68.2 % of spring PSZ accessions and in 80 % of winter and 55 % of spring VIR accessions. The analysis of genotypes showed the presence of 13 different allelic combinations of the Glu-A1, Glu-B1, Glu-D1 genes in the PSZ varieties, and 19 combinations in the VIR varieties. The b b/al/с d allelic combination (Ax2* Вх7+Ву8/8*/9 Dx5+Dy10) turned out to be the most common for the PSZ spring varieties and lines, while for the PSZ winter accessions it was a с d (Ax1 Вх7+By9 Dx5+Dy10); the b с a and b с d genotypes (Ax2* Вх7+Ву9 Dx2+Dy12 and Ax2* Вх7+Ву9 Dx5+Dy10, respectively) occur with equal frequency among the VIR spring accessions; in the group of VIR winter varieties, the combination of the a b/   al d alleles (Ax1 Вх7+Ву8/8* Dx5+Dy10) prevails. The most preferred combination of alleles for baking qualities was found in the spring variety ‘Ekaterina’ and winter varieties ‘Tarasovskaya 97’, ‘Volzhskaya S3’, as well as in lines k-58164, L43510, L43709, L-67, L-83, which are recommended for further breeding programs to improve and preserve baking qualities in the conditions of the Pre-Ural steppe zone.